Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1021/jp971520s
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Internal Rotational Barriers in Furfural. NMR Measurements and ab-Initio Molecular Orbital Methods Using Continuum Models

Abstract: Modern experimental and theoretical methods for determining solvent effects on internal rotational barriers in small molecules are compared. The barrier to rotation of the aldehyde group in furfural dissolved in toluene, acetone, and methanol is used as a test case. Ab-initio molecular orbital methods such as self consistent reaction field (SCRF) calculations, performed with the Onsager and isodensity surface polarized continuum (IPC) model, predict an increase in barrier with increasing solvent dielectric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 71 publications
(208 reference statements)
5
34
0
Order By: Relevance
“…Here, the average number and the strength of hydrogen bonds formed between the solute and the solvent are essentially constant along the internal rotation, giving again no contribution to the activation entropy. These results are in fair agreement with previous observations from Bain and Hazendonk [28] for the investigation of furfural in methanol.…”
Section: Hydrogen Bonding Patternssupporting
confidence: 93%
See 2 more Smart Citations
“…Here, the average number and the strength of hydrogen bonds formed between the solute and the solvent are essentially constant along the internal rotation, giving again no contribution to the activation entropy. These results are in fair agreement with previous observations from Bain and Hazendonk [28] for the investigation of furfural in methanol.…”
Section: Hydrogen Bonding Patternssupporting
confidence: 93%
“…Recently, Baldridge et al [12] showed that the conformer with larger dipole moment, OOcis, prevails in solvents with dielectric constants higher than 5. However, the stability between both conformers does not obey a simple relationship with the dielectric constant [28]. This, of course, indicates that the solvent effects are more complex than could be inferred by a simple reaction field.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The conformational equilibrium between planar forms of furfural (Fig. 1) has received special attention in both experimental and theoretical articles,1–14 including the effect of solvent on the OO‐cis/OO‐trans population ratio and on rotational barriers. The relative facility for the industrial production of this compound from pentose‐rich biomass and its two well‐defined, self‐exchangeable and stable isomers have sparkled imagination as a prospect for a single molecule bit of information storage.…”
Section: Introductionmentioning
confidence: 99%
“…37 The cavity surface of a molecular solute is usually defined either as a union of atomic spheres, 38 often with additional constructions to fill in the regions where adjacent spheres intersect, 39,40 or as a solute electronic isodensity contour. 5,19,41,42 In practice, these prescriptions may not differ too much from one another. We prefer the isodensity contour construction, which automatically provides a smooth surface and is completely specified by a single parameter, namely the numerical value chosen for the contour.…”
Section: Introductionmentioning
confidence: 99%